Do Human Rights Derive from Natural Rights? the State of Nature, Political Authority and the Natural Right to Independence - Montero, Julio César (2016)
In this article I examine whether human rights may revive from natural rights. I will start by briefly considering some of the main objections formulated against the natural rights approach in order to show that human rights cannot be equated to natural rights. However, after examining the political approach, I also expect to prove that there are compelling reasons not to discard the natural rights perspective altogether. In particular, I will argue that human rights may be grounded on a natural right to independence: a right not to be subjugated or treated as instruments by others. This is not a right to be provided with secure access to protections, resources and opportunities. It is rather a purely negative right to set and pursue our own aims provided we let others do the same. I will then proceed to explain why the view I am suggesting may accommodate the main features of current human rights practice, why it may justify a reasonable list of human rights, and why it may account for the international dimension that human rights are considered to have under present international law. Finally, in the conclusion, I will highlight some important implications of my argument.